The effectiveness of the action-oriented approach in the teaching of the plural -s, possessive-s and third person singular inflectional endings to improve the speaking skills of seventh graders at Colegio Ambientalista de Pejibaye, Jiménez - Rojas Sánchez, Ismael 1992- (2020)
This research analyzes whether or not the Action-Oriented Approach was effective for teaching the inflectional endings plural -s, possessive -s and third person singular in order to improve the speaking skills of a group of high school students (7th graders) at Colegio Ambientalista de Pejibaye, Cartago, Costa Rica. The purpose of the investigation rose from the necessity of knowing the reality about the effectiveness of the implementation of this new approach during academic English lessons. This study was focused on the development of this new approach by the design and the application of six sessions that involved the development of the Action-Oriented Approach in a real classroom of seventh graders. The level of the groups was chosen because during primary school, they had no contact with this new approach. For this investigation, a quasi-experimental design was chosen because the groups (7-2 and 7-3) were already established by the high school since the beginning of the year. Before implementing the teaching sessions, an observation was done in order to verify that the principles of the Action-Oriented Approach were applied by the cooperating teacher. The teaching sessions were planned by the researchers according to the Action- Oriented Approach for the experimental group and the Communicative Approach for the control group. Then, two oral tests (pre and post) were applied by the researchers to measure participants' initial and final performance, and six teaching sessions (each session consisted of three lessons of forty minutes per week for a total of eighteen lessons. These sessions were supposed to be carried out in seven weeks, but because of extracurricular activities, it took 14 weeks). Another group was selected which represented the control group (dealt with a different approach: the Communicative Approach). The results suggested a higher performance by the experimental group after being intervened, and an analysis on how participants...